Synthesis and characterization of a novel nonlinear optical hyperbranched polymer containing a highly performing chromophore. (30th January 2013) - Cabanetos, Clément; Bentoumi, Wissam; Blart, Errol; Pellegrin, Yann; Montembault, Véronique; Bretonnière, Yann; Andraud, Chantal; Mager, Loic; Fontaine, Laurent; Odobel, Fabrice
<x xml:space="preserve">Abstract</x> We report herein the peripheral functionalization of a high glass transition temperature hyperbranched polyimide with a new and highly performing electro‐optic chromophore for the elaboration of a second‐order nonlinear optical material. In this study, the CPO1 chromophore was selected for its very high quadratic hyperpolarizability coefficient (μβ = 31, 000 ⋅ 10−48 esu at 1990 nm) and its ease of synthesis in multigram scale. As a result, the new electro‐optic polymer was characterized by an r33 coefficient around 40 pm/V at 1.5 µm, although the poling conditions were not optimized. For sake of comparison, the electro‐optic r33 coefficient of our previously reported similar polymer functionalized with the well‐known Disperse Red One chromophore was also measured using the technique and gave a much lower r33 coefficient. This study underscores that hyperbranched polymers are particularly promising matrices to host highly efficient chromophore to achieve more efficient and more stable electro‐optic devices than classical linear polymers. Copyright © 2013 John Wiley & Sons, Ltd.